Siamese and triplet network-based pain expression in robotic avatars for care and nursing training - Lee, Miran; Lee, Minjeong; Kim, Suyeong (Frontiers in Robotics and AI, 2024)
Care and nursing training (CNT) refers to developing the ability to effectively respond to patient needs by investigating their requests and improving trainees’ care skills in a caring environment. Although conventional CNT programs have been conducted based on videos, books, and role-playing, the best approach is to practice on a real human. However, it is challenging to recruit patients for continuous training, and the patients may experience fatigue or boredom with iterative testing. As an alternative approach, a patient robot that reproduces various human diseases and provides feedback to trainees has been introduced. This study presents a patient robot that can express feelings of pain, similarly to a real human, in joint care education. The two primary objectives of the proposed patient robot-based care training system are (a) to infer the pain felt by the patient robot and intuitively provide the trainee with the patient’s pain state, and (b) to provide facial expression-based visual feedback of the patient robot for care training.